Mechanisms of glycerol electroreduction on activated carbon-based electrodes / Siti Aqilah Nadhirah Md. Rahim - Siti Aqilah Nadhirah, Md. Rahim (2022)
Glycerol generated from biodiesel manufacture is a beneficial waste that can be potentially used to synthesize valuable products via the low-cost and simple setup method, namely electrolysis. This waste can produce oxygenated and reduced compounds through electrooxidation and reduction reactions, respectively. This work aims to study the reaction mechanisms of glycerol electroreduction in the cathode region using inexpensive activated carbon-based electrodes. The experiments were divided into three sections. The first part is to synthesize the activated carbon composite (ACC) electrodes with various activated carbon compositions. The influence of different activated carbon percentages (60%, 70%, 80%, and 90%) of the total weight in the ACC electrodes on the physicochemical and electrochemical properties was explored by field emission scanning electron microscopy and energy-dispersive X-ray spectroscopy (FESEM-EDX), cyclic voltammetry (CV), and chronoamperometry (CA) analyses. Results indicated that high activated carbon content portrayed a dominant role in controlling an electroactive surface area (EASA), and the electrons transfer process which eventually improved the electrocatalytic activity. 80ACC outperformed other ACC electrodes by generating Amberlyst-15 anionic radicals (A-15•- ) with the highest EASA (36.7 cm2 ) and current density (-0.2018 A/cm2 ) at low potential. A-15•- served as the electron-donor for the homogeneous redox reaction with glycerol in delivering highly reactive glycerol radical for further intermediates development and generated 1,2-propanediol. Meanwhile, the low activated carbon percentage preferred diethylene glycol formation. Acetol and ethylene glycol were subsequently suggested as the intermediates for 1,2-propanediol and diethylene glycol formation, which were produced from the dissociation of glycerol either through the C-C bond or C-O bond cleavage, respectively. Hence, in the second part, the proposed intermediates were employed as the glycerol substitutes to elucidate the overall reaction mechanisms of glycerol electroreduction on the 80ACC electrode. Data proved 80ACC in Amberlyst-15 redox mediator solution demonstrated a superior activity for acetol electro-hydrogenation into 1,2-propanediol. At 80 °C, 1,2-propanediol selectivity (with 59.8 C mol% yield) reached 77.3% at the 7 th hour using 3.0 M of acetol and 0.28 A/cm2 current density. Whereas diethylene glycol was acquired through intermolecular dehydration of ethylene glycol in the Amberlyst-15 solution without electricity. Besides, H + ions from Amberlyst-15 are advantageous in facilitating glycerol conversion to a selective acetol. Lastly, the preliminary experiments for glycerol electroreduction to study the effects of reaction temperature (27-106.5 °C), initial glycerol concentration (0.3-4.35 M), and current density (0.07-0.28 A/cm2 ) on the reaction were carried out. Findings revealed the generation of acetol, and ethylene glycol intermediates was profoundly controlled by the temperature where a mild value is needed to maintain a selective acetol 1,2-propanediol route. Additionally, a moderate glycerol initial concentration reduced the hydrogen formation and indirectly improved 1,2-propanediol yield. A medium current density raised the conversion rate and minimized the intermediates growth. At 80.0 °C and 0.21 A/cm2 , glycerol (3.0 M) electroreduction to 1,2-propanediol reached the maximum yield of 42.3 C mol%. The experimental value obtained was close to the predicted yield (41.8 C mol%) from the polynomial model developed using response surface methodology (RSM) and analysis of variance (ANOVA).